Sahl ibn Harun the Writer: His Historical Narrations and Political Impact - AlThaalibi, Ali AbdulHussein (Thi Qar Arts Journal, 2025)
Sahl ibn Harun was a Persian figure who lived during the early Abbasid era. He was renowned for his literature, eloquence, and wisdom, earning the title of "the Wise." He authored many works, most of which are lost. He witnessed the reigns of three Abbasid caliphs: Al-Rashid, Al-Amin, and Al-Ma'mun. He worked with Al-Rashid as a supervisor of the House of Wisdom and served as a writer for Al-Ma'mun, also supervising the House of Wisdom. He contributed to narrating the history of significant events of that period, including the tragedy of the Barmakids and the conflict between Al-Amin and Al-Ma'mun. Additionally, he made important contributions to political thought and provided political advice to kings and their associates.